Peasant articulation to the market: the case of Putinza (middle CañeteValley, Lima) - Rodríguez Castillón, Juan (2010)
During the decades of the 1950’s and 1960’s, several communitiesof Peru’s central coastal area, well-known examples being Acos andHuayopampa (Chancay Valley, Huaral), converted from subsistenceproduction systems to fruit growing, economically more profitable.This occurred in Putinza, the community discussed in this paper.Around 1955 it shifted to cultivating fruit and replaced multicroppingwith monoculture, articulated to the urban markets of Cañete andLima. This research, which combines field work with a diachronicand synchronic vision and draws on comparative studies of peasanteconomies, seeks to explain the factors that facilitated this articulationin the early 1960’s. Among the factors that influenced thisprocess are the ecological advantages the community enjoyed, itsopenness to change, its relative closeness to large urban centers,the existence of roads and infrastructure, and market advantages interms of prices and the growing consumer demand for fruit.